2020
DOI: 10.3390/ma13143103
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymer Inclusion Membranes Doped with Alkylimidazole to Separation of Silver and Zinc Ions from Model Solutions and after Battery Leaching

Abstract: New materials, such as polymer inclusion membranes, can be used for water and wastewater treatment. In this paper, the selective transport of silver(I) and zinc(II) ions from nitrate solutions through the polymer inclusion membranes (PIMs), which consist of cellulose triacetate as a polymeric support, o-nitrophenyl pentyl ether as a plasticizer, and either 1-hexylimidazole (1) or 1-hexyl-2-methylimidazole (2) as an ion carrier, is studied. Both Zn(II) and Ag(I) model solutions (CM = 0.001 M, pH = 6.5), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Therefore, it should be concluded that this equation (Equation 3) is inapplicable i.e., the assumption of linearity is incorrect and the model is inadequate. It should be noted that incorrect distribution of residuals was also observed in the results presented by other authors for the transport of various substances in PIM and SLM systems [3,10,[13][14][15][16]. In order to avoid this problem, a number of researchers select initial points for which the linearity of Equation 3and normality of distribution is maintained.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, it should be concluded that this equation (Equation 3) is inapplicable i.e., the assumption of linearity is incorrect and the model is inadequate. It should be noted that incorrect distribution of residuals was also observed in the results presented by other authors for the transport of various substances in PIM and SLM systems [3,10,[13][14][15][16]. In order to avoid this problem, a number of researchers select initial points for which the linearity of Equation 3and normality of distribution is maintained.…”
Section: Resultsmentioning
confidence: 98%
“…In the above equation, V f denotes the volume of the feed solution (m 3 ), A-an area of membrane (cm 2 ), c f -the concentration of a substance at the given time t in the feed solution [mol/cm 3 This model is primarily applied for quick calculation of the initial flux (J i , mol/cm 2 s)-a parameter which describes the transport efficiency and corresponds to the maximum flux observed in the membrane system:…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations